Coherent dipoles in a mixed layer with variable buoyancy: Theory compared to observations. (September 2020) - Lahaye, Noe; Zeitlin, Vladimir; Dubos, Thomas
Abstract: Motivated by recent observations of coherent dipolar cyclone–anticyclone structures in the ocean, the modons, and their signature in the surface temperature field, we demonstrate that the classical modon solutions of the barotropic quasi-geostrophic equations can be generalized to include buoyancy or temperature as an active tracer. The properties of such "thermal" modons, and especially their ability to carry heat anomaly over long distances, depend on the relative sign of the associated vorticity and buoyancy anomalies. We show using numerical simulations with the thermal shallow water equations, and their quasi-geostrophic version, that the evolution of the modons is consistent with the observations. Highlights: Existence of coherent dipolar vortices is demonstrated in thermal shallow water model. The evolution of these vortices is consistent with recent observations. Their transport and mixing properties depend on relative signs of vorticity and buoyancy anomalies.